Exploring Peacebuilding Strategies to Develop Teacher-Student Interpersonal Relationships in English as a Foreign Language/English as a Second Language Classrooms - Fu, Jiangtao (Frontiers in Psychology, 2021)
In the conflict-affected era, there is now an urgent need for a peaceful world. Although the relevance of peace in language education, within English as a second language (ESL) or English as a foreign language (EFL), may seem irrelevant to some, the language of peace utilizes an interdisciplinary method that supports students in creating more reasonable discussions. Alternatively, the attention of language teaching is just on the development of cognition in preference to emotions whereas methods that sustain the theory of the whole person through positive psychology should be presupposed. This review seeks to explore the connection between multiple dimensions of peace and the certain strategies and activities that can be implemented to build peace in EFL/ESL classrooms. Further, the related strategies and activities on the issues such as self-regulation, engagement, mindfulness, and motivations are proposed. In a nutshell, the implications of peacebuilding for teachers, teacher-trainers, and future researchers are presented, and new directions for future research are set out.